Dynamics of Manganese and Cerium Enrichments in Arctic Ocean Sediments: A Case Study From the Alpha Ridge - Ye, Liming; März, Christian; Polyak, Leonid; Yu, Xiaoguo; Zhang, Weiyan (Frontiers in Earth Science, 2019)
Manganese (Mn) and cerium (Ce) are known as reactive metals sensitive to marine redox conditions, and can therefore serve as useful proxies for paleoceanographic environments. Quaternary sedimentary records in the Arctic Ocean show a consistent cyclicity of Mn enrichments, but Mn sources, transportation and deposition patterns, and relationship to paleoclimatic conditions are not well understood. Sediment core ARC3-B85D from the Alpha Ridge with the estimated stratigraphy covering ~350 kyr is used to investigate a coupled distribution of Mn and Ce in Quaternary Arctic Ocean sediments. By analyzing Mn and Ce distribution patterns in the core and surface sediments from the western Arctic Ocean and adjacent shelves, we investigate the conditions and dynamics of concurrent metal enrichments. Stratigraphic Ce and Mn patterns follow inferred glacial-interglacial cycles, with enrichments generally occurring during interglacial-type conditions with high sea levels. However, the relationships involved are not straightforward as highest Mn and Ce enrichments seem to occur closer to the end of interglacial/major interstadial periods, when sea levels were lowering from their highest positions. We conclude that the enrichment patterns are primarily defined by sediment dynamics controlling resuspension and transportation of reactive metals and their deposition in the central Arctic Ocean after diagenetic preconditioning on the shelves. We further infer that major transportation agents are sea-level affected cross-shelf and mid-depth ocean currents rather than sea ice as has been proposed earlier. Comprehending this coupled geochemical and sedimentary system is important for improving the chronostratigraphic framework for Quaternary deposits in the Arctic Ocean.